MENGEMBANGKAN RESILIENSI REMAJA DALAM UPAYA MENGATASI STRES SEKOLAH - Desmita Desmita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
School today are facing the difficult challenges of ensuring success for all students and fostering an empowered, enthusistic staff of lifelong. This article is about developing “resiliency”, a new paradigma of student development that offers schools a coherent. The foundation for the resiliency paradgma is a dramatic new perspective on how children and adolescence bounce back from stress, trauma, and risk in their lives that is emerging from the fields of psychiatry, psychology, and sociology. An understanding of resiliency, its importance, and the way schools can help students bounce back and evolve into more competent and successful learners is needed now more than ever. In this article, resiliency is defined and six-step plan of action for resiliency building is introduced.Kata Kunci: resiliensi remaja, mengatasi stress sekolah